2005
DOI: 10.1002/ijc.20932
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cancer and risk of second malignancies in young cancer patients in Trieste, Italy

Abstract: We carried out a cohort study in the Italian province of Trieste (2001 population, 242,000) to ascertain whether the risk of a subsequent primary cancer among 265 individuals diagnosed with a first malignancy at ages up to 25 years between 1971 and 1993 differed from that in the general population and to evaluate the effect of cancer family history, quantified by the family risk index (FRI), on the occurrence of second primaries. During the follow-up (median duration = 10 years; 25th-75th percentile = 2-16), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
3
0
2
Order By: Relevance
“…The removal of duplicates resulted in 574 potentially relevant articles from which 53 were selected based on title and abstract. Of those 19 met the inclusion criteria and were included in this review 11–29. Reasons for exclusion of the remaining 34 articles are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The removal of duplicates resulted in 574 potentially relevant articles from which 53 were selected based on title and abstract. Of those 19 met the inclusion criteria and were included in this review 11–29. Reasons for exclusion of the remaining 34 articles are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies observed SMN and malignant melanoma as SMN in a population of CCS who could have had any type of childhood cancer 14, 20, 22, 36. Brunetti et al 14 reported that 265 CCS developed 14 times more malignant melanomas than would be expected [standardized incidence ratio (SIR) of 14.3 (95% CI: 1.7–51.6)]. Friedman et al 36 described a SIR of 3.3 (95% CI: 2.4–4,5) for being diagnosed with a malignant melanoma as SMN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Отягощенный ЗН семейный анамнез является бес-спорным фактором риска для развития многих опухо-лей [7,18]. Показано, что отягощенный семейный анамнез значимо повышает риск развития как ПМСО, так и ПММО с поражением яичников.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…Существует обратная связь между степенью по-вседневной физической активности и риском разви-тия РЯ [18,19]. Женщины с ПМЗН (как ПМСО, так и ПММО) чаще занимались умственным трудом по сравнению со здоровыми женщинами.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified